1997
DOI: 10.1159/000190247
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage during Hemodialysis Using a Vitamin-E-Modif ied Dialysis Membrane: A Preliminary Characterization

Abstract: A comparison of the oxyradical exposure during hemodialysis (HD) carried out with vitamin-E-modified cellulose (CL-E) or conventional membranes, studying red blood cell (RBC) and plasma lipoperoxidation and RBC glutathione metabolism, was done. In this preliminary characterization of a new and original approach to the prevention of free radical damage in HD, the results obtained indicate that lipoperoxidation in plasma and RBC is decreased and therefore oxidative damage can be significantly decreased using CL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 5 publications
0
53
1
1
Order By: Relevance
“…surface of the dialysis membrane 28,29 but not by systemic antioxidant effects of vitamin E eluted from the dialyzer. In summary, hemodialysis per se impairs endothelial function, possibly by increasing oxidative stress.…”
Section: Miyazaki Et Al Hemodialysis-induced Endothelial Dysfunctionmentioning
confidence: 92%
See 2 more Smart Citations
“…surface of the dialysis membrane 28,29 but not by systemic antioxidant effects of vitamin E eluted from the dialyzer. In summary, hemodialysis per se impairs endothelial function, possibly by increasing oxidative stress.…”
Section: Miyazaki Et Al Hemodialysis-induced Endothelial Dysfunctionmentioning
confidence: 92%
“…28,29 With this dialyzer, it has been shown that the consumption of blood antioxidants, oxidative demolition of lipids, and activation of leukocytes were significantly attenuated. 28,29 Accordingly, we hypothesized that hemodialysis per se may impair endothelial function and that hemodialysis using a vitamin E-coated dialyzer may restore endothelial dysfunction.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly with early studies [20, 30], vitamin E bound to the dialysis membrane surface has been observed to be active in redox cycling accessory antioxidants such as ascorbic acid [31, 32]. This basic finding, together with a possible even if minimal release of vitamin E during HD, might justify the observation of a supplementation effect [20, 21]probably mainly due to a sparing effect on the constitutive pool of blood vitamin E. These standing points in understanding the bioreactive properties of the vitamin E-bonded membranes go together with other papers showing how these membranes can improve some antioxidant parameters [32], lower lipid peroxidation both in vitro and in vivo [31, 33, 34, 35, 36]and slow down advanced glycation end-products (AGEs) accumulation [34].…”
Section: Introductionmentioning
confidence: 93%
“…Although lipid peroxidation has been reported to be raised in hemodialysis patients, most studies have used the thiobarbituric acid test, which is known to have low specificity and to produce artefacts when applied to body fluids [13, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38]. Despite the claim this test evaluates lipid peroxidation by measuring only malonaldehyde, a hydroperoxide degradation product [39], it also reacts with many other components, among them amino acids, sugar, biliverdin, hemoglobin, prostaglandin, thromboxanes, therapeutics agents, and even urea [40, 41, 42, 43, 44].…”
Section: Discussionmentioning
confidence: 99%